2019
DOI: 10.1016/j.htct.2018.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiografic abnormalities in patients with sickle cell/β-thalassemia do not depend on the β-thalassemia phenotype

Abstract: Objectives and methods We evaluated possible relationships between echocardiographic findings and clinical and laboratory parameters, in a cohort of Brazilian patients diagnosed with sickle cell/β-thalassemia, to better understand the cardiac involvement in this disease. Results Left atrial (LA) and left ventricular (LV) dilation were found in 19.5 and 11% of patients, respectively; systolic left ventricular dysfunction was present in a single patient. There were no dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Accordingly, an Arab study showed that Sβ-thal were more likely to be on HU therapy than SCD homozygous patients, noting that they featured a more severe phenotype [3]. Moreover, previous studies showed a lower prevalence of atrial dilation in Sβ-thal than SCD homozygous patients [36,56]. It is known that the atrial myocardium is more sensitive to iron deposition and anemia than the ventricle [40], and this could explain the higher left atrial area in the less frequently HU-treated SCA group, as well as the absence of significantly different biventricular volumes between Sβ-thal and SCA patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, an Arab study showed that Sβ-thal were more likely to be on HU therapy than SCD homozygous patients, noting that they featured a more severe phenotype [3]. Moreover, previous studies showed a lower prevalence of atrial dilation in Sβ-thal than SCD homozygous patients [36,56]. It is known that the atrial myocardium is more sensitive to iron deposition and anemia than the ventricle [40], and this could explain the higher left atrial area in the less frequently HU-treated SCA group, as well as the absence of significantly different biventricular volumes between Sβ-thal and SCA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of this study is that we did not have sufficient information on the quantitative β-globin defect of Sβ-thal patients (β0 or β+ mutation), and we also did not assess the hemoglobin A percentage, which could have been useful in better characterizing our population. Nevertheless, a recent study compared echocardiographic parameters of a group of Sβ-thal patients with β+ thalassemia mutation with those with β0 mutation [36]. They concluded that cardiac involvement in patients with sickle beta thalassemia does not appear to depend on the type of beta mutation, but the presence of signs of myocardial remodelling appears to be linked to multiorgan deficiency.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of this complex diagnosis scenario, there is a group of patients with a double heterozygosity of SCD and βT, which leads to the clinical expression of a variant of SCD. This condition has a considerable prevalence in Brazil and cardiac alterations of a sample of these patients were studied by Benites et al 16 and presented at this journal. There were no cardiac geometry alterations neither differences in LV systolic function between SCD variant patients and controls when evaluated by conventional echocardiographic indexes.…”
mentioning
confidence: 99%